Clinical Cases in Skin of Color Medical, Oncological and Hair Disorders, and Cosmetic Dermatology - Love, Porcia B.; Kundu, Roopal V. (Clinical Cases in Dermatology, 2016)
This book identifies the most common presentations and essential features of top dermatological conditions in patients with skin of color. It presents practical information in a case-based organization to assist dermatologists in clinical decision making, and discusses important cultural beliefs that must be considered in order to provide optimal care to patients with skin of color. There is an increasing demand for dermatologic treatments in patients with skin of color, as well as an accompanying need for education and training in this quickly expanding market. Skin of color is a key topic within dermatology as specific conditions can be harder to diagnose effectively in darker skin, and patients' treatment can be compromised by this. Clinical Cases in Skin of Color: Medical, Oncological and Hair Disorders, and Cosmetic Dermatology is a concise resource with practical guidance for board certified dermatologists and dermatologists in training.